1994
DOI: 10.1093/ajcn/59.3.600
|View full text |Cite
|
Sign up to set email alerts
|

The Copenhagen Cohort Study on Infant Nutrition and Growth: breast-milk intake, human milk macronutrient content, and influencing factors

Abstract: In 91 healthy term infants breast-milk intake was measured at 2, 4, and 9 mo by test weighing and human milk macronutrient content by infrared analysis every 2-4 wk. In infants exclusively breast-fed, mean milk intake was 781 and 855 mL/24 h at 2 and 4 mo, respectively, and correlated positively with the current weight of the infant and negatively with the amount of formula supplement given at the maternity ward. Median daily energy intake was considerably below current recommendations (423 and 381 kJ/kg body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
2
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 39 publications
10
82
2
2
Order By: Relevance
“…However, prior research has shown extensive variation in maternal behaviors that determine infant access to milk (Gray, 1995;Vitzthum, 1994). Jenness, 1979;Mandel et al, 2005;Michaelson et al, 1994;Nommsen et al, 1991 Water (86.0-88.0 g) Ogra et al, 2006;Vaughan et al, 1979 Fat (2.5-6.0 g) Brown et al, 1986;Mitoulas et al, 2002;Nommsen et al, 1991;Prentice et al, 1981a;WHO, 1985 Myristic acid (14:0) Palmitic acid (16:0) Linoleic acid (18:2n-6) Alpha-linolenic acid (18:3n-3) Arachidonic acid (20:4n-6) Docosahexaenoic acid (22:6n-3) Protein (0.83-1.30 g) Brown et al, 1986;Mitoulas et al, 2002;Nommsen et al, 1991;Prentice et al, 1981a;WHO, 1985 In addition to inter-individual variation, there is considerable variation in milk production within an individual woman, and even within a single feed (Daly et al, 1993a;Kent et al, 2006). Foremilk, the first milk expressed during a feeding, is usually relatively dilute and low in fat compared with hindmilk (Daly et al, 1993a), the last milk consumed during in a feeding bout.…”
Section: Sources Of Variation In Human Milkmentioning
confidence: 99%
“…However, prior research has shown extensive variation in maternal behaviors that determine infant access to milk (Gray, 1995;Vitzthum, 1994). Jenness, 1979;Mandel et al, 2005;Michaelson et al, 1994;Nommsen et al, 1991 Water (86.0-88.0 g) Ogra et al, 2006;Vaughan et al, 1979 Fat (2.5-6.0 g) Brown et al, 1986;Mitoulas et al, 2002;Nommsen et al, 1991;Prentice et al, 1981a;WHO, 1985 Myristic acid (14:0) Palmitic acid (16:0) Linoleic acid (18:2n-6) Alpha-linolenic acid (18:3n-3) Arachidonic acid (20:4n-6) Docosahexaenoic acid (22:6n-3) Protein (0.83-1.30 g) Brown et al, 1986;Mitoulas et al, 2002;Nommsen et al, 1991;Prentice et al, 1981a;WHO, 1985 In addition to inter-individual variation, there is considerable variation in milk production within an individual woman, and even within a single feed (Daly et al, 1993a;Kent et al, 2006). Foremilk, the first milk expressed during a feeding, is usually relatively dilute and low in fat compared with hindmilk (Daly et al, 1993a), the last milk consumed during in a feeding bout.…”
Section: Sources Of Variation In Human Milkmentioning
confidence: 99%
“…28 It is well established that the fat content is higher in hind-milk (53.3 g/l) than in foremilk (24.5 g/l) 29 but that it does not change dramatically with stage of lactation. 28,29 Information available on the impact of the variation of fat and energy content of breast milk on growth and adiposity during infancy and later in life are limited to small, short-term studies due to the practical constraints of appropriate frequent milk sampling and longterm follow-up. In a study with a small group of only six infants, growth rate was not related to fat and energy intake during the first 6 months of life.…”
Section: Pre-and Post-natal Recommendations Of Dietary Fat Levelsmentioning
confidence: 99%
“…20 These values are similar to those reported from other laboratories. 25 The acceptability of HOP to study mothers was uniformly positive, as >90% of mothers saw their production increase from pre-to post-instruction by an average of 48% (583 ± 383 to 863±506; P<0.0003). The high caloric value of milk could not be appreciated but may be a motivational factor for advising future mothers to use the technique.…”
Section: Discussionmentioning
confidence: 89%